2014
DOI: 10.1136/vetreccr-2014-000086
|View full text |Cite
|
Sign up to set email alerts
|

An unusual presentation of Chlamydia pneumoniae infection in a Royal Python (Python regius)

Abstract: Chlamydia species are a relatively newly recognised and emerging pathogen in reptile species. Chlamydia pneumoniae has been reported to cause infections in several snake species, as well as other reptiles and amphibia, leading to granulomatous lesions in multiple organs, enteritis, pneumonia‐like signs and generalised condition loss. In this case the snake presented with anorexia, severe loss of condition and the neurological sign of loss of its righting reflex. No pneumonia‐like clinical signs were present. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…62,63 An unusual case of C. pneumoniae infection was recently described in a royal python showing neurological signs. 34 Histology revealed lymphocytic enteritis with histiocytic granulomas, granulomatous splenitis and meningitis. Chlamydial IHC was positive in splenic granulomas and PCR identified C. pneumoniae in pooled visceral tissues.…”
Section: Chlamydial Infections In Reptilesmentioning
confidence: 98%
“…62,63 An unusual case of C. pneumoniae infection was recently described in a royal python showing neurological signs. 34 Histology revealed lymphocytic enteritis with histiocytic granulomas, granulomatous splenitis and meningitis. Chlamydial IHC was positive in splenic granulomas and PCR identified C. pneumoniae in pooled visceral tissues.…”
Section: Chlamydial Infections In Reptilesmentioning
confidence: 98%
“…Organs commonly affected are the spleen, heart, lung and liver, and diagnosis is usually on the basis of visualisation of the inclusions by light or electron microscopy. In many cases, proliferative pneumonia was observed prior to euthanasia or natural death of reptiles (Bodetti et al, 2002), and limited cases have reported inflammation or lesions in the gastrointestinal tract, wasting disease, necrotising mycocarditis, necrotising enteritis and splenitis (Bodetti et al, 2002;Jacobson et al, 2002;Jacobson et al, 2004;Cope et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…The infection typically manifests as inflammatory lesions in affected organs (granulomatous inflammation) (Howerth, 1984;Homer et al, 1994). In many cases, proliferative pneumonia was observed prior to euthanasia or natural death of reptiles (Bodetti et al, 2002), and limited cases have reported inflammation or lesions in the gastrointestinal tract, wasting disease, necrotising mycocarditis, necrotising enteritis and splenitis (Bodetti et al, 2002;Jacobson et al, 2002;Jacobson et al, 2004;Cope et al, 2014). In many cases, proliferative pneumonia was observed prior to euthanasia or natural death of reptiles (Bodetti et al, 2002), and limited cases have reported inflammation or lesions in the gastrointestinal tract, wasting disease, necrotising mycocarditis, necrotising enteritis and splenitis (Bodetti et al, 2002;Jacobson et al, 2002;Jacobson et al, 2004;Cope et al, 2014).…”
Section: Introductionmentioning
confidence: 99%